Penser la pluralité des monnaies à partir de Polanyi : un essai de typologie - Blanc, Jérôme (ERES, 2014)
A large number of currencies has emerged for thirty years, far beyond the national currencies alone. It includes systems created by groups of citizens, others by territorial communities, and others by private companies for their own benefit. These currencies take various forms, ranging from electronic money on smart cards to settlement systems ...
Sociology
Keywords: currencies; modern currencies

The double movement and new labor market regulations in Korea, Japan, and Taiwan - Yun, Ji-Whan (A comparative study of East Asian capitalism, 2014)
Political Science
Keywords: Japan; Korea; Taiwan; consolidation; diverging paths; double movement; dual labour markets; economics; labour; labour market reforms; politics and government; systemic change